La migración latinoamericana actual en el cine mexicano y argentino - Paola García; Perla Petrich (Les Cahiers ALHIM)
Mexican cinema traditionally has tended to the dramatic quality and to the presentation of the emigrant as a tragic victim.  Argentinian cinema for your part has been characterized by a sentimentality dyed of certain humor. Both of them have resorted to the stereotypes and to a unidimensional vision. Nevertheless, in spite of the fact that there are very different contexts, nowadays cinematographic productions of both countries tend to complicate the subject matter, to show other aspects, besides poverty and dictatorships, which motivate  migration and  lack of integration. In some recent movies a decrease of the fictional aspect is observed in favour of an almost documentary approach. In others there is a change of kind:  "drama" is left behind and they are catalogued as " dramatic comedies " and even romantic comedies or simply movies of great comedy.The main purpose of this article is  to expose these changes and their motivations.